A medical geography of endemic goiter in central java - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1987)
In short, the case study village, already a recipient of iodine supplement efforts is clearly one where the endemic goiter has a large component of active goitrogens in the diet. Prophylaxis based entirely on the hypothesis of absolute iodine deficiency can be overridden by excess iodine. A recommendation is made for government health planners and agencies to carefully investigate the possibility of goitrogens in the diet at the time of the initial goiter survey. A goiter prevention policy should then be develoved for each community which includes an appropriate emphasis on iodine supplements and diet modification.